Participative approach to elicit water quality monitoring needs from stakeholder groups – An application of integrated watershed management. (15th July 2018) - Behmel, S.; Damour, M.; Ludwig, R.; Rodriguez, M.J.
Abstract: Water quality monitoring programs (WQMPs) must be based on monitoring objectives originating from the real knowledge needs of all stakeholders in a watershed and users of the resource. This paper proposes a participative approach to elicit knowledge needs and preferred modes of communication from citizens and representatives of organized stakeholders (ROS) on water quality and quantity issues. The participative approach includes six steps and is adaptable and transferable to different types of watersheds. These steps are: (1) perform a stakeholder analysis; (2) conduct an adaptable survey accompanied by a user-friendly public participation geographical information system (PPGIS); (3) hold workshops to meet with ROS to inform them of the results of the survey and PPGIS; discuss attainment of past monitoring objectives; exchange views on new knowledge needs and concerns on water quality and quantity; (4) meet with citizens to obtain the same type of input (as from ROS); (5) analyze the data and information collected to identify new knowledge needs and modes of communication and (6) identify, in collaboration with the individuals in charge of the WQMPs, the short-, medium- and long-term monitoring objectives and communication strategies to be pursued. The participative approach was tested on two distinct watersheds in the province of Quebec, Canada. It resulted in a series of optimization objectives of the existing WQMPs, new monitoring objectives and recommendations regarding communication strategies of the WQMPs' results. The results of this study show that the proposed methodology is appreciated by all parties and that the outcomes and monitoring objectives are acceptable. We also conclude that successful integrated watershed management is a question of scale, and that every aspect of integrated watershed management needs to be adapted to the surface watershed, the groundwater watershed (aquifers) and the human catchment area. Highlights: Transferable participative approach to elicit knowledge needs on water quality. Optimal water quality monitoring based on objectives from a participative approach. Optimized communication strategies based on results from a participative approach. Inclusive participative approaches are welcome to all types of stakeholders. Successful integrated watershed management is a question of scale.